2019
DOI: 10.2134/cftm2018.10.0085
|View full text |Cite
|
Sign up to set email alerts
|

Early Planting Dates Maximize Soybean Yield in Kentucky

Abstract: Core Ideas Harvested plant population was reduced with April and early‐May planting dates. Greater soybean seeding rates are needed for April and early‐May planting dates. Seed yield was greatest for April and early‐May planting dates. Relative yield loss/day was 0.50% after 8 May in MG IV cultivars. In Kentucky, the optimum planting window for soybean [Glycine max (L.) Merr.] was mid‐May to mid‐June for more than 30 years. This is despite recent work in the United States indicating that April to May plantin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…Decisions based on recommendations given by seed dealers or Extension guides assume average weather. With increased climate variability, there is a need to continually update planting recommendations to improve the decision‐making process (Knott, Herbek, & James, ). Currently there is a knowledge gap regarding maturity selection when planting is delayed past the optimum planting window.…”
Section: Introductionmentioning
confidence: 99%
“…Decisions based on recommendations given by seed dealers or Extension guides assume average weather. With increased climate variability, there is a need to continually update planting recommendations to improve the decision‐making process (Knott, Herbek, & James, ). Currently there is a knowledge gap regarding maturity selection when planting is delayed past the optimum planting window.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural crop production is closely related to crop phenological change. Previous research presented that the optimum range of crop phenological stages can lead to high crop production [58]. Some studies suggested that warming climate advanced phenological phases and, consequently, shortened crop growth duration, potentially reducing crop yield [2,19].…”
Section: Effects Of Crop Phenological Shift On Crop Yieldmentioning
confidence: 99%
“…Different management practices and decisions have been shown to contribute to soybean yield variation. These practices include the following: planting dates, row spacing, weed control and herbicide use, measures taken to reduce harvest losses (Specht et al., 1999) and seeding rates (Knott et al., 2019). In an effort to assess the causes of soybean yield gaps in agricultural areas in the North‐Central U.S., Edreira et al.…”
Section: Early Planting As a Key Practice To Increase Soybean Yieldmentioning
confidence: 99%
“…In Kentucky, for more than 30 years, the optimum planting window for soybean was considered as mid‐May to mid‐June; however, Knott et al. (2019) found that late April to early May planting dates maximized soybean seed yield. In studies from Illinois, Indiana, Iowa and Ontario in 2013 and 2014, Kandel et al.…”
Section: Early Planting As a Key Practice To Increase Soybean Yieldmentioning
confidence: 99%
See 1 more Smart Citation